Assessment of Body Mass Index (BMI) in Under-graduate Medical Students - Farah, Shayela; Ferdousi , Jannatul; Nayem, Mohammad; Karim, Mohoshina (Journal of Dhaka National Medical College & Hospital, 2015)
Background: Dietary habits and physical activity play an important role in maintaining a healthy body mass index. Studies among medical students worldwide report high burden of underweight (10 to 20.5%) and obesity (11.7 to 23.1%). Objective: To assess the nutritional status of the undergraduate medical students in Dhaka city. Methodology: The present study was a descriptive type of cross sectional study conducted at Dhaka Community Medical College and Hospital, Dhaka during February to April 2014. The target population consisted of 287 students from first, second year and third year (age 19-21 years) was included. Results: Of total 287 students, 152(53%) were male and 135 (47%) female. About half of the respondents were found with healthy weight 139 (48.43%) whereas obese and overweight were respectively 58(20.21%), 33 ( 11.50%) with average BMI 21.7245 (±3.485). Statistically highly significant (p <0.001) relationship between BMI category and sex, educational status of the students were found. Conclusion: Awareness programme are needed to rectify the situation so the students can have normal BMI and decreased incidence of clinical problems associated abnormal BMI. J. Dhaka National Med. Coll. Hos. 2015; 21 (02): 46-50